Two novel mutations in apolipoprotein C3 underlie atheroprotective lipid profiles in families. (24th June 2013) - Bochem, A.E.; van Capelleveen, J.C.; Dallinga‐Thie, G.M.; Schimmel, A.W.M.; Motazacker, M.M.; Tietjen, I.; Singaraja, R.R.; Hayden, M.R.; Kastelein, J.J.P.; Stroes, E.S.G.; Hovingh, G.K.
<x xml:space="preserve">Abstract</x> Apolipoprotein C3 (APOC3) mutations carriers typically display high plasma high‐density lipoprotein cholesterol (HDL‐C) and low triglycerides (TGs). We set out to investigate the prevalence and clinical consequences of APOC3 mutations in individuals with hyperalphalipoproteinemia. Two novel mutations (c.‐13‐2A>G and c.55+1G>A) and one known mutation (c.127G>A;p.Ala43Thr) were found. Lipid profiles and apoCIII isoform distributions were measured. c.55+1G>A mutation carriers displayed higher HDL‐C percentiles (35.6 ± 35.8 vs 99.0 ± 0, p = 0.002) and lower TGs (0.51 (0.37–0.61) vs 1.42 (1.12–1.81) mmol/l, p = 0.007) and apoCIII levels (4.24 ± 1.57 vs 7.33 ± 3.61 mg/dl, p = 0.18). c.‐13‐2A>G mutation carriers did not display significantly different HDL‐C levels (84.0 ± 30.0 vs 63.7 ± 45.7, p = 0.50), a trend towards lower TGs [0.71 (0.54 to 0.78) vs 0.85 (0.85 to –) mmol/l, p = 0.06] and significantly lower apoCIII levels (3.09 ± 1.08 vs 11.45 ± 1.06 mg/dl, p = 0.003). p.Ala43Thr mutation carriers displayed a trend towards higher HDL‐C percentiles (91.2 ± 31.8 vs 41.0 ± 29.7 mmol/l, p = 0.06) and significantly lower TGs [0.58 (0.36–0.63) vs 0.95 (0.71–1.20) mmol/l, p = 0.02] and apoCIII levels (4.92 ± 2.33 vs 6.60 ± 1.60, p = 0.25). Heterozygosity for APOC3 mutations results in high HDL‐C and low TGs and apoCIII levels. This favourable lipid profile in patients with genetically low apoCIII levels holds promise for current studies investigating the potential of apoCIII inhibition as a novel therapeutic in cardiovascular disease prevention.